Depression in Parkinson’s Disease – Profile and Assessment - Desislava Marinova; Maya Danovska; Yoanna Todorova; Trayana Obreshkova (Journal of Biomedical & Clinical Research)
Depression and anxiety are the most common nonmotor symptoms in Parkinson‘s disease-NMSPD in the department of the neuropsychiatric disorders. Depression is present in all stages of PD - early and advanced even in premorbid stage of PD. The incidence of depression in PD varies in large limits according of used methods and criterions. Some somatic symptoms are part of the depression syndrome. At the presence no consensus exists about the etiology of depression in PD. The concomitant occurrence of depression and PD and the overlapping symptomatology of PD and depression usually lead to the terminological discussion and discrepancy. To explain the high prevalence of depression in PD some hypotheses have been proposed. Many scales were used for assessment of depression in PD. The properties and critique of nine scales was discussed.